Respuesta :

Answer:

f(-2) = 1

Step-by-step explanation:

Let the given table represents a function f(x).

Input values of the function has been denoted by x values and output values by f(x).

In other words,

For input value x = (-6),

Output value, f(-6) = 3

For input value x = (-2),

Output value, f(-2) = 1

For input value x = 0,

Output value f(0) = 4

For input value x = 3,

Output value, f(3) = -2

Therefore, for input value x = (-2), output value of the function will be f(-2) = 1

ACCESS MORE